2006
DOI: 10.1210/en.2005-0907
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-Like Peptide Stimulates Food Intake via Activation of Neuropeptide Y Neurons in the Hypothalamic Dorsomedial Nucleus of the Rat

Abstract: Galanin-like peptide (GALP), a 29-amino-acid neuropeptide, is located in the hypothalamic arcuate nucleus (ARC), binds to galanin receptor subtype 2, and induces food intake upon intracerebroventricular (icv) injection in rats. However, neural mechanisms underlying its orexigenic action remain unclear. We aimed to identify the nuclei and neuron species that mediate the food intake in response to icv GALP injection. Intracerebroventricular injection of GALP, as powerfully as that of neuropeptide Y (NYP), increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…56 Furthermore, inhibition of endogenous NPY or NPY receptors suppresses GALP-induced acute orexigenic effect in rats. 55 These findings suggest that GALP promotes feeding behavior through suppression of the anorexigenic pro-opiomelanocortin system and NPY release from the DMH. Our recent experimental data suggest that the orexigenic actions of GALP are mediated by orexin in the LHA, based on the electromicroscopic observation that GALP-positive axon terminal appears to have made synapse with orexinpositive perikaryon and dendritic process in the rat LHA.…”
Section: Feeding and Energy Metabolism By Galp S Shioda Et Almentioning
confidence: 87%
See 2 more Smart Citations
“…56 Furthermore, inhibition of endogenous NPY or NPY receptors suppresses GALP-induced acute orexigenic effect in rats. 55 These findings suggest that GALP promotes feeding behavior through suppression of the anorexigenic pro-opiomelanocortin system and NPY release from the DMH. Our recent experimental data suggest that the orexigenic actions of GALP are mediated by orexin in the LHA, based on the electromicroscopic observation that GALP-positive axon terminal appears to have made synapse with orexinpositive perikaryon and dendritic process in the rat LHA.…”
Section: Feeding and Energy Metabolism By Galp S Shioda Et Almentioning
confidence: 87%
“…54 NPY release in the DMH has been proposed to have a role in mediating the effects of GALP on feeding regulation, 55 although another study reported no such effect. 56 Furthermore, inhibition of endogenous NPY or NPY receptors suppresses GALP-induced acute orexigenic effect in rats.…”
Section: Feeding and Energy Metabolism By Galp S Shioda Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…However, it does not appear ARC POMC/CART or NPY/ AgRP neurons are involved in mediating GALP's effects on fertility, as GALP was not able to directly modulate their activity (Kuramochi et al 2005). In contrast, NPY neurons in the dorsomedial nucleus of the hypothalamus were shown to mediate GALP's acute orexigenic feeding actions (Kuramochi et al 2006), suggesting GALP and NPY neurons may exhibit bi-directional communication to coordinate their effects on feeding behavior and fertility.…”
Section: Galp-expressing Neuronsmentioning
confidence: 96%
“…Anti-obesity Effect of GALP GALP was initially described as an orexigenic neuropeptide given that administration of GALP into the brain induces food intake for the first hour thereafter in rats [35][36][37][38]. We previously reported that c-Fos immunoreactivity is increased in orexin-immunoreactive neurons in the LH after the central administration of GALP [39].…”
Section: Regulation Of Galp Mrna Expressionmentioning
confidence: 99%